Albert Demangeon (1872-1940). Sources et bibliographie - Denis Wolff (Cybergeo, 2005)
This bibliography stems from a doctoral research on the French geographer Albert Demangeon. It consists of an inventory, first, of the sources available, and then, of his published works sorted chronologically, indicating new editions and translations (if applicable), and listing reviews of his books.